Material Choices: Refashioning Bast and Leaf Fibers in Asia and the Pacific - E. N. Anderson (Ethnobiology Letters, 2010)
Review of Material Choices: Refashioning Bast and Leaf Fibers in Asia and the Pacific. Roy W. Hamilton and B. Lynne Milgram, eds. 2008. Fowler Museum at UCLA, Los Angeles. Pp. 187, bibliography, index, copious color illustrations. $30.00 (paper). ISBN-13 9780974872988.